An online community peer support intervention to promote COVID-19 vaccine information among essential workers: a randomized trial. (31st December 2022) - Ugarte, Dominic Arjuna; Lin, Jeremy; Qian, Tianchen; Young, Sean D.
Abstract: Introduction: Vaccine hesitancy is still rampant in the United States, including health care personnel. Vaccination of frontline essential workers (e.g. health care workers) is very important, especially during a pandemic. We tested the efficacy of a 4-week online, peer-led intervention (Harnessing Online Peer Education) to promote requests for COVID-19 vaccine information among essential workers. Methods: Participants ( N  = 120) and peer leaders ( N  = 12) were recruited through online advertisements from July 23 to August 20, 2021. Eligibility criteria included: 18 years or older, U.S. resident, English speaker, part of phase 1a or 1 b of COVID-19 vaccine rollout (e.g. frontline essential workers), hadn't received a COVID-19 vaccine but able to receive one. This was a parallel assignment randomised trial. STATA was used to create a randomisation using a random number generator so that all possible assignments of participants and peer leaders to groups were equally likely. Participants were randomly assigned to intervention or control arms that consisted of two private, hidden Facebook groups, each with 30 participants. Peer leaders were randomly assigned to an intervention group, each with six peer leaders. Participants in the intervention arm were randomly assigned to three peer leaders. Participants were blinded after assignment. Peer leaders were tasked with reaching out to their assigned participants at least three times each week. Participants completed a baseline and a post intervention survey. The study is registered on ClinicalTrials.org under identifier NCT04376515 and is no longer recruiting. This work was supported by the NIAID under grant 5R01AI132030-05. Results: A total of 101 participants analysed (50 intervention and 51 control). Six people in the intervention group and 0 people in the control group requested vaccine information. Ten people in the intervention group and six people in the control group provided proof of vaccination. The odds of requesting vaccine information in the intervention group was 13 times that in the control group (95% confidence interval: (1.5, 1772), p -value = 0.015). Thirty-seven participants in the intervention group and 31 in the control group were engaged at some point during the study. Conclusions: Results suggest peer-led online community groups may help to disseminate health information, aid public health efforts, and combat vaccine hesitancy. Key Messages: The odds of requesting vaccine information was 13 times in the intervention group. Peer-led online communities may help to disseminate information and aid public health efforts to combat vaccine hesitancy.